The Relationship Between Diet and Physical Activity With Quality of Life In The Elderly In Glintang Village, Sambi Boyolali District - Putri Nabilah Rochmaningrum; Risky Ika Riyani; Ika Dyah Kurniati; Muslimah Muslimah (International Journal of Health and Pharmaceutical (IJHP), 2025)
Elderly are those who have reached the age of 60 and over. Central Java is one of eight provinces in Indonesia that has entered the old population structure, with the percentage of the elderly population reaching 14.17%, and will continue to increase every year. An increase in the quantity of the elderly must be balanced with an increase in the quality of life of the elderly. There are several factors that may affect a person's quality of life, such as eating patterns and physical activity. The purpose of this study was to determine the relationship between eating patterns and physical activity with quality of life in the elderly in Glintang Village, Sambi Boyolali District. This study used cross-sectional analytic observation, with 46 elderly respondents. The data was processed using rank-spearman test. The questionnaires in this study used the Food Frequency Questionnare (FFQ), the Global Physical Activity Questionnare (GPAQ), and the WHOQOL-BREF Questionnare. The results of the analysis using the rank-spearman test showed that there was no relationship between eating patterns and the quality of life of the elderly with a p=0.359 (p>0.05) and there was a relationship between physical activity and the quality of life of the elderly with a value of p=0.001 (p <0.05). The majority of the elderly in Glintang Village, Sambi Boyolali District have good BMI, eating patterns, physical activity, and quality of life. There is no relationship between eating patterns and quality of life in the elderly and there is a relationship between physical activity and quality of life in the elderly in Glintang Village, Sambi Boyolali District.